A STUDY ON MOTIVATION AND JOB SATISFACTION WITH REFERENT TO WARE HOUSE MANAGEMENT - Poongavanam, S. (International Journal of Supply Chain Management, 2018)
The present study investigates the relationship between Motivation and Job Satisfaction. Motivation has been treated as an important factor in the company and has a significant impact on Job Satisfaction. The respondents were contact during the lunch break; convenience sampling techniques is used to select the sample size of 100. t Primary data has been collected by the researcher through structured questionnaires. Keywords-work climate, flow of information, flexibility and freedom of work. Job satisfaction, warehouse management